2011
DOI: 10.1099/mic.0.045393-0
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of dichloroaniline isomers by a newly isolated strain, Bacillus megaterium IMT21

Abstract: An efficient 3,4-dichloroaniline (3,4-DCA)-mineralizing bacterium has been isolated from enrichment cultures originating from a soil sample with a history of repeated exposure to diuron, a major metabolite of which is 3,4-DCA. This bacterium, Bacillus megaterium IMT21, also mineralized 2,3-, 2,4-, 2,5-and 3,5-DCA as sole sources of carbon and energy. These five DCA isomers were degraded via two different routes. 2,3-, 2,4-and 2,5-DCA were degraded via previously unknown dichloroaminophenol metabolites, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…Similarly, Canton et al [11] also classified 2-C-4-NA as a blacklist substance due to its poor biodegradability. However, based on the previous reports on the biodegradation of structural analogues of 2-C-4-NA such as 4-nitroaniline, 2-, 3-, 4-chloroaniline and 3, 4-dichloroaniline, possibilities for the biodegradation of 2-C-4-NA by microorganisms could also be presumed [12][18]. In this communication, we report metabolic characterization of 2-C-4-NA by Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 86%
“…Similarly, Canton et al [11] also classified 2-C-4-NA as a blacklist substance due to its poor biodegradability. However, based on the previous reports on the biodegradation of structural analogues of 2-C-4-NA such as 4-nitroaniline, 2-, 3-, 4-chloroaniline and 3, 4-dichloroaniline, possibilities for the biodegradation of 2-C-4-NA by microorganisms could also be presumed [12][18]. In this communication, we report metabolic characterization of 2-C-4-NA by Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 86%
“…B. megaterium has earlier been reported for its potential against various pollutants such as PAH (polycyclic aromatic hydrocarbons), dyes and chromium. [36,37] Its bifunctional Cytochrome P450 enzyme has been highlighted by various catabolic studies. [38] Thus, strains KKc3, KKc4 and KKc6 detoxified endosulfan, whereas KKc7 followed the toxic endosulfan sulphate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria often possess the ability to degrade xenobiotic compounds (Vamsee-Krishna et al, 2006;Cycon et al, 2009). The degradation of propanil by the rice rhizosphere bacteria shows that these organisms had adapted to metabolize this chemical after repeated rounds of exposure in the field (Sarkar et al, 2010;Yao et al, 2011). Earlier studies have suggested that pesticides applied to soil are often degraded more rapidly following repeated application to the same site, where the soil then possesses bacteria capable of degrading the contaminants (Witzig et al, 2006).…”
Section: Discussionmentioning
confidence: 99%